2022
DOI: 10.1093/ofid/ofac213
|View full text |Cite
|
Sign up to set email alerts
|

Progression to Critical Illness and Death in Patients With Breakthrough Hospitalizations

Abstract: Background Characterization of disease progression and outcomes after COVID-19-related hospitalization in vaccinated compared with unvaccinated individuals is limited. Methods Retrospective case-control study of symptomatic vaccinated (cases) and unvaccinated (controls) participants hospitalized for COVID-19 between December 30, 2020 and September 30, 2021 in Southeast Michigan. Hospitalized adult patients with lab-confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…Moreover, patients with hybrid immunity were older and more likely to have underlying comorbidities than those with natural immunity. However, the median number of comorbidities was lower in patients with reinfection compared with breakthrough infections or hospitalization [35] , [36] . Immunocompromised patients who are at higher risk for breakthrough infections and reinfection represented almost a quarter of our cohort and had higher odds of disease progression, findings that were similar to previous reports [17] , [29] , [35] , [36] , [39] , [7] .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Moreover, patients with hybrid immunity were older and more likely to have underlying comorbidities than those with natural immunity. However, the median number of comorbidities was lower in patients with reinfection compared with breakthrough infections or hospitalization [35] , [36] . Immunocompromised patients who are at higher risk for breakthrough infections and reinfection represented almost a quarter of our cohort and had higher odds of disease progression, findings that were similar to previous reports [17] , [29] , [35] , [36] , [39] , [7] .…”
Section: Discussionmentioning
confidence: 88%
“…In contrast to breakthrough or postvaccine infections [24] , [25] , [35] , [38] , [39] , reinfections are more commonly reported in younger persons [13] , [18] , [24] , [25] , [3] , [31] , [4] . In the present study, the patient population was also younger, with a median age of 41 years.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Suleyman et al, showed vaccinated patients with breakthrough infection had reduced mortality (11%) as compared to unvaccinated patients (24.9%) ( p < 0.001), although the severity of illness was similar between study participants based on the modified SOFA score [ 21 ]. Lower mortality observed in the study could be due to inclusion of all the patients requiring hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…While the above observations are extremely important for COVID-19-related healthcare planning and for briefing the general public on the benefits of vaccination, they are unable to answer a clinically relevant question whether patients hospitalised with COVID-19 have different mortality and other outcomes by vaccination status. Most studies investigating in-hospital mortality by vaccination status provide unadjusted estimates with varying results from beneficial [ 8 14 ], through neutral [ 15 18 ] to harmful [ 19 , 20 ] effects of vaccination. Given the fact that most countries prioritised high-risk patients (the elderly, those with comorbidities) for vaccination [ 21 ], these unadjusted estimates may reflect local factors and are less helpful for risk stratification of admitted patients.…”
Section: Introductionmentioning
confidence: 99%